The mu-opioid receptor gene polymorphism 118A>G depletes alfentanil-induced analgesia and protects against respiratory depression in homozygous carriers - Oertel, Bruno G; Schmidt, Ronald; Schneider, Andreas; Geisslinger, Gerd; Lötsch, Jörn (Pharmacogenetics and genomics, 2006)
To investigate whether OPRM1 118A>G polymorphism affects analgesic and respiratory depressive effects of alfentanil and assess its role for the therapeutic range of alfentanil. In an open-label, single-occasion design, 10 non-carriers, four heterozygous and six homozygous carriers of the variant OPRM1 118G allele received a computerized infusion of alfentanil to achieve target effect-site concentrations of 0, 33.33, 66.67 and 100 ng/ml. At each concentration level, analgesia was assessed by means of electrically and chemically induced pain, and respiratory depression was quantified by hypercapnic challenge and breathing frequency. The relationship between the percent change of tolerance to electrical stimuli and measured alfentanil concentrations, described by power models, was flatter in carriers of the 118G variant allele than in non-carriers, indicating decreased opioid analgesia (P<0.05). For chemically induced pain, a flatter analgesia versus concentration relationship was found only for homozygous carriers of the 118G allele (P<0.05). The relationship between the percent changes in respiratory parameters was significantly flatter (P<0.01) only in homozygous carriers as compared to heterozygous carriers and non-carriers of the 118G allele. Higher alfentanil concentrations were needed in homozygous carriers as compared to wild-type subjects (2-4 times) to produce the same degree of analgesia, whereas 10-12 times higher alfentanil concentrations were needed to produce the same degree of respiratory depression. OPRM1 118A>G polymorphism affects both analgesic and respiratory depressive effects of alfentanil. However, while the analgesic effects are already partly decreased in heterozygous carriers, depending on the pain model, the respiratory depressive effects are decreased in homozygous carriers of the variant 118G allele. The therapeutic range of alfentanil was only broadened in homozygous carriers.